Diseño de una unidad de deslinealización y desnormalización para un sistema de optimización de energía de uso en paneles fotovoltaicos - Rojas-Salazar, Juan José (Instituto Tecnológico de Costa Rica, 2016)
In this work, a general delinearization-denormalization unit for an energy optimization system of photovoltaic panels was implemented. The unit is based on the IEEE754 standard, and uses the CORDIC algorithm. A suitable implementation is provided in HDL. Post Place & Route simulations (resources, power, timming report) and functional veri cation in an FPGA are also given with a maximum error of 0.5 % for both current (Is) and voltage (α) parameters.
Proyecto de Graduación (Licenciatura en Ingeniería Electrónica) Instituto Tecnológico de Costa Rica. Escuela de Ingeniería Electrónica, 2016.
Keywords: HDL; FPGA; CORDIC; Verilog; Aritmética Binaria